Collapse of Breeding Success in Desert-Dwelling Hornbills Evident Within a Single Decade - Pattinson, Nicholas B.; van de Ven, Tanja M. F. N.; Finnie, Mike J.; Nupen, Lisa J.; McKechnie, Andrew E.; Cunningham, Susan J. (Frontiers in Ecology and Evolution, 2022)
Rapid anthropogenic climate change potentially severely reduces avian breeding success. While the consequences of high temperatures and drought are reasonably well-studied within single breeding seasons, their impacts over decadal time scales are less clear. We assessed the effects of air temperature (Tair) and drought on the breeding output of Southern Yellow-billed Hornbills (Tockus leucomelas; SYBH) in the Kalahari Desert over a decade (2008 – 2019). We aimed to document trends in breeding performance in an arid-zone bird during a time of rapid climate warming and identify potential drivers of variation in breeding performance. Breeding output of our study population collapsed during the monitoring period. Comparing the first three seasons (2008 – 2011) of monitoring to the last three (2016 – 2019), the mean percentage of nest boxes occupied declined from 52% to 12%, nest success from 58% to 17%, and mean fledglings produced per breeding attempt from 1.1 to 0.4. Breeding output was negatively correlated with increasing days on which Tmax (mean maximum daily Tair) exceeded the threshold Tair at which male SYBHs show a 50% likelihood of engaging in heat dissipation behaviour (i.e. panting [Tthresh; Tair = 34.5 °C]) and the occurrence of drought within the breeding season, as well as later dates for entry into the nest cavity (i.e. nest initiation) and fewer days post-hatch spent incarcerated in the nest by the female parent. The apparent effects of high Tair were present even in non-drought years; of the 115 breeding attempts we recorded, all 18 attempts which had ≥ 72% days during the attempt on which Tmax > Tthresh failed (equivalent to Tmax during the attempt ≥ 35.7 °C). This suggests climate warming was likely the primary driver of the recent, rapid breeding success collapse. Based on current warming trends the Tmax threshold of 35.7 °C, above which no successful breeding attempts were recorded, will be exceeded during the entire SYBH breeding season by approximately 2027 at our study site. Our findings therefore support the prediction that climate change may drive rapid declines and cause local extinctions despite the absence of direct lethal effects of extreme heat events.